Determining the Environmental Effects of Indirect Subsidies - Cees van Beers; Jeroen C.J.M. van den Bergh; André de Moor; Frans Oosterhuis (Tinbergen Institute, 2004)
Up to now a clear theoretical and methodological framework for economic-environmental analysis of environmentally damaging subsidies is lacking. Environmentally damaging subsidies are all kinds of direct and indirect subsidies aimed at achieving a certain (often non-environmental) goal that produce negative external effects to the natural environment. This article develops a transparent method to determine the environmental impact of indirect government subsidies and derive policy lessons. This method has been applied to several major subsidies in the Netherlands, namely in agriculture, energy, and transport. The results reveal large environmental effects, which need to be taken seriously by policy makers. The method enables policy makers to evaluate the environmental impacts of indirect government subsidies.
Keywords: H2; Q2; Q3; Q5; Q28; 330; subsidies; environmental economics; environmental management; policy; Subvention; Umweltbelastung; Wirkungsanalyse